1988
DOI: 10.1063/1.99020
|View full text |Cite
|
Sign up to set email alerts
|

Hole photoionization cross sections of EL2 in GaAs

Abstract: The spectral dependence of the hole photoionization cross section σ0p of EL2 in GaAs has been determined in absolute numbers at T=78 and 295 K. From simultaneous measurements of the electron photoionization cross section σ0n, accurate values of the photon energies and the cross sections at which σ0n=σ0p could be obtained. These data are of importance for rapid and accurate determination of concentration and charge states of EL2 in GaAs, e.g., in wafer mapping applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(52 citation statements)
references
References 10 publications
3
49
0
Order By: Relevance
“…The known quantities are n ϭ0.907 ϫ 10 Ϫ16 cm 2 for 1.1 m light, 8,9 v n ϭͱ8kT/ m n *ϭ4.16ϫ10 7 cm/s, and Cϭ2.6ϫ10 6 cm Ϫ3 , all valid at 300 K.…”
Section: ͑3͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The known quantities are n ϭ0.907 ϫ 10 Ϫ16 cm 2 for 1.1 m light, 8,9 v n ϭͱ8kT/ m n *ϭ4.16ϫ10 7 cm/s, and Cϭ2.6ϫ10 6 cm Ϫ3 , all valid at 300 K.…”
Section: ͑3͒mentioning
confidence: 99%
“…The concentration of electrons excited per unit time is I 0 n N EL2 0 , where n , the optical ͑photo-ionization͒ cross section for EL2, is well known. 8,9 The steady-state concentration of electrons is I 0 n N EL2 0 n , where n is the lifetime. Since the photoexcited electron is removed from the conduction band by being trapped at an EL2 ϩ center, we can write…”
mentioning
confidence: 99%
“…In our experiments we use an additional infrared (IR) laser to influence the field F. The excitation energy of the IR laser, hν IR = 1.240 eV, is considerably less than the lowest transition energy of the sample studied and, accordingly, can not simultaneously excite both electrons (e's) and holes (h's), but can generate solely either e's or h's by excitation of deep level (DL) defects positioned in the band gap of the CaAs barriers [22]. According to our model, these extra carriers, excited by the IR laser, will effectively screen the field F and will consequently slow down the carrier transport in the plane of the WL.…”
Section: Introductionmentioning
confidence: 99%
“…[10] II. EXPERIMENT The sample investigated in this work consisted of a nominally undoped 1×1×2 cm 3 GaAs block containing 1.45× 10 16 cm −3 EL2 centers, as determined by optical absorption spectroscopy [12], and a carbon concentration of the order of 1×10 16 cm −3 , estimated from FFT-IR absorption. [13] The spectral analysis revealed that essentially all EL2 were in the normal state at room temperature.…”
Section: Introductionmentioning
confidence: 99%